Analysis between Vaccination Status and Gender with Level of Confidence to Use of Covid-19 Vaccination in Community - Athiya Adibatul Wasi; Diansanto Prayoga; Syifaul Lailiyah; Jayanti Dian Eka Sari; Mohammad Zainal Fatah; Ajeng Febrianti Rahayu (Universitas Airlangga, 2022)
Background: The cases of Covid-19 in Indonesia continues to increase, various policies have been set by the government to prevent cases increase, one of which is the implementation of the vaccination program. However, there are still people who are hesitant or afraid to COVID-19 vaccination. Based on a survey conducted by the Indonesian Ministry of Health in 2021, some of the most common reasons for refusing the COVID-19 vaccine are related to vaccine safety (30%); doubts about the effectiveness of the vaccine (22%); distrust of vaccines (13%); concern about side effects such as fever and pain (12%); and religious reasons (8%).Objectives: To Analyze the relationship between vaccination status and gender with level of confidence to use of Covid-19 vaccination in the community.Methods: Observational research using a survey approach, cross-sectional study design. The population is adults who access the Healthy People Mall program in Banyuwangi, with a total sample of 437. Conducted from March to October 2021. Collecting data by studying literature and distributing online questionnaires using google forms. The level of confidence is obtained from the total score of 3 confidence indicators. Processing and analysis of research data using the Chi-square test.Results: 87.8% of females and 82% of males were vaccinated. A significant relationship between the level of confidence to use of the Covid-19 vaccine and vaccination status (P-value = 0.000), and no relationship between the level of confidence to use of the Covid-19 vaccine and gender (P-value = 0.124).Conclusions: The Majority of people who access the Healthy People Mall in Banyuwangi are vaccinated. The proportion of vaccinated, women is higher than men. The variable that has a relationship with the level of confidence in the use of the Covid-19 vaccine is vaccination status, while gender does not have a relationship.